Effect of a pronunciation learning management learning system among student of different language anxiety levels - Soon Fook Fong; Fei Ping Por (2016)
The purpose of this study was to investigate the effects of three presentation modes of ‘epronounce’ in learning correct pronunciation with phonetic symbols among non-native English speakers with different language anxiety levels. The ‘epronounce’ which is an interactive multimedia pronunciation learning management system, was designed and developed with three presentation modes (Text + Sound + Phonetic Symbols[TSP], Text + Sound + Phonetic Symbols + Mouth Movements[TSPM], Text + Sound + Phonetic Symbols + Face Gestures[TSPF]) to address the needs of non-native English speakers with low, medium and high language anxiety in improving their pronunciation. The nature of pronunciation learning is a source of language anxiety. Non-native English speakers in particular, are very self-conscious when interacting with others in second/foreign language that might expose their inadequacies. The presentation modes acted as independent variable, while the dependent variable was the mean score of posttest. The moderator variable was the different language anxiety levels. The sample of the study was 329 Primary Five Malaysian students from three different schools. Descriptive statistics and inferential statistics were carried out to analyse the research data. Analyses of Covariance (ANCOVA) were used to study the main effects and the interaction effect of independent variables against the dependent variables. The findings of this study showed that there are no significant interaction effects between language anxiety levels and presentation modes of epronounce’. Seemingly ‘epronounce’ is able to bring the students to medium language anxiety level and hence optimizing pronunciation learning, which is in line with the curvilinear relationship between anxiety and performance.